Nuclear functions of heterogeneous nuclear ribonucleoproteins A/B - He, Yaowu; Smith, Ross (Cellular and molecular life sciences : CMLS, 2009)
The hnRNP A/B proteins are among the most abundant RNA-binding proteins, forming the core of the ribonucleoprotein complex that associates with nascent transcripts in eukaryotic cells. There are several paralogs in this subfamily, each of which is subject to alternative transcript splicing and post-translational modifications. The structural diversity of these proteins generates a multitude of functions that involve interactions with DNA or, more commonly, RNA. They also recruit regulatory proteins associated with pathways related to DNA and RNA metabolism, and appear to accompany transcripts throughout the life of the mRNA. We have highlighted here recent progress in elucidation of molecular mechanisms underlying the roles of these hnRNPs in a wide range of nuclear processes, including DNA replication and repair, telomere maintenance, transcription, pre-mRNA splicing, and mRNA nucleo-cytoplasmic export.